The Construction of Fair and Civilized Humanitarian Values in the Concept of Sipakatau in Bugis Society in Bone Regency - Agustan, Agustan; Indra, Andi Batara; Darwis, Muh.; T, Irma; Suardi, Putri (Universitas of Muhammadiyah Makassar, 2024)
Acts of violence and social conflict continue to color the life of the nation and state in Indonesia. This study aims to describe and analyze the fair and civilized human values constructed in the concept of sipakatau and the human values that influence individual and community behavior in Bugis society in Bone Regency. This research used a qualitative research design with a case study approach. Research data were collected through observation, in-depth interviews, and documentation studies. The results of this study show that (1) the value of a just and civilized humanity in the concept of sipakatau through pangadereng which has elements of sadda (voice), ada (words), gau deeds, ade (custom), tau (human); (2) human values that influence individual and community behavior in society through; cultural values, social values, educational values, and religious values. Bugis society, especially in Bone, refers to the concept of pangadereng, which is a form of culture that includes systems, norms and rules of life in the community.